PENERAPAN TEKNIK RELAKSASI BENSON DALAM UPAYA STABILISASI KADAR GLUKOSA DARAH PADA PASIEN DIABETES MILITUS DI RUANG ARAFAH RUMAH SAKIT UNIVERSITAS AHMAD DAHLAN - Hanindya Riefki Kumala Devi; Sriyati (JOURNAL SAINS STUDENT RESEARCH, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion, where unmanaged instability of blood glucose levels can trigger various serious complications. One non-pharmacological intervention that can be used to help stabilize blood sugar is the Benson relaxation technique, which combines deep breathing relaxation with elements of belief or spirituality. This final nursing scientific paper aims to analyze the application of the Benson relaxation technique in an effort to stabilize blood glucose levels in patients with Diabetes Mellitus through a nursing care approach. The method used was a case study of a DM patient experiencing blood glucose instability, with the intervention carried out over 3 days, lasting 15–20 minutes per session. The evaluation results showed that after routine intervention, there was a reduction and stabilization of the patient's random blood glucose levels, as well as an increased sense of calm and relaxation. This reduction occurs because Benson relaxation can suppress sympathetic nervous system activity and reduce the production of cortisol, a hormone involved in gluconeogenesis. In conclusion, the Benson relaxation technique is effective as a complementary therapy in the management of Diabetes Mellitus patients. Nurses are encouraged to integrate this technique into independent nursing care to help manage patients' blood glucose holistically.